Management of psoriasis in pregnancy – a review of the evidence to date - Ferreira, Clara (Drugs Context, 2020)
The onset of psoriasis collides with women’s reproductive timeframe, and pregnancy brings challenges to its treatment. Indeed, the health of both mother and foetus must be considered. When choosing to treat pregnant women affected by psoriasis with pharmacological therapy, it is important to be aware of all possible options and their repercussions. Although there are several pharmacological therapies available, pregnancy brings ethical concerns and any pharmacological approach must be well thought out. The data available in humans are limited, and further investigation on this matter is needed. Within biological therapies, certolizumab pegol has recently been identified as a promising approach during pregnancy because it has been shown to have no late active placental transfer and no clear signs of foetal harm. This article aims to review the impact of psoriasis during pregnancy, how the disease can be managed pharmacologically during this period according to the available armamentarium, and the possible effects of the therapeutic options for the mother and the foetus.